Sinking, Shrinking, Satin Island. - Quarrie, Cynthia (Journal of Modern Literature)
Tom McCarthy has been singled out more than once as a model for the future of the novel, but he is rarely discussed in terms of his national context, except as an avant-garde exception to a persistent narrative of British national and literary decline. In his novel Satin Island, however, McCarthy addresses his Britishness and the problem of his literary exceptionalism through the figure of the writer-as-anthropologist, through which he maps an ethico-political relationship to the history of British imperialism. This in turn shines a light on the disavowed, depoliticized melancholias of pre- and post-Brexit Britain as they circulate within the field of contemporary British literature. McCarthy spatializes and materializes post-colonial melancholy and makes it readable as shame.